• Dec 16th 2009, 04:28 PM
kayteee92
Log3x – log3 (x-5) = log3 A
Express A in terms of x.
Hence, solve the equation
Log3 x – log3 (x-5) = 1

Thank you so much.
• Dec 16th 2009, 04:29 PM
kayteee92
every single 3 is a base, it just didn't show up.
• Dec 16th 2009, 04:31 PM
Jhevon
Quote:

Originally Posted by kayteee92
Log3x – log3 (x-5) = log3 A
Express A in terms of x.
Hence, solve the equation
Log3 x – log3 (x-5) = 1

Thank you so much.

Recall that $\displaystyle \log_a X - \log_a Y = \log_a \frac XY$

So that,

$\displaystyle \log_3 x - \log_3 (x - 5) = \log_3 A$

$\displaystyle \Rightarrow \log_3 \frac x{x - 5} = \log_3 A$

Now what?
• Dec 16th 2009, 05:08 PM
kayteee92
oh okay, so next i did

A = x/x-5

and i crossed multiplied to get x = A(x-5)

but for the next part of the problem, i replaced this for x and now i am stuck.

• Dec 16th 2009, 08:58 PM
Jhevon
Quote:

Originally Posted by kayteee92
oh okay, so next i did

A = x/(x-5)

stop there. that is A in terms of x.

Quote:

but for the next part of the problem, i replaced this for x and now i am stuck.